Nogué, Joan; Puigbert, Laura i Bretcha, Gemma (eds.) (2008): Paisatge i salut - Mota Moya, Pau (Documents d'Anàlisi Geogràfica, 2012)
Nogué, Joan; Puigbert, Laura i Bretcha, Gemma (eds.) (2008) Paisatge i salut Olot: Observatori del Paisatge. Barcelona: Generalitat de Catalunya. Departament de Salut ISBN: 978-84-612-4858-2